2021
DOI: 10.1002/jmv.27140
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL‐32 rs28372698 polymorphism with active chronic HBV infection

Abstract: Interleukin-32 (IL-32), a multiple proinflammatory cytokine, plays a vital role in immune-related diseases and infectious diseases. The promoter region of IL-32, which showed functional polymorphism, could regulate IL-32 expression. Although IL-32 rs28372698 polymorphism has been related to a lot of inflammatory diseases, the association of IL-32 rs28372698 polymorphism with a hepatic flare of chronic HBV infection has not been reported. In the present study, IL-32 rs28372698 polymorphism was genotyped in 104 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Recently, several studies have demonstrated the impact of IL-32 polymorphisms on cancer progression. Moreover, IL-32 SNPs were studied and reviewed with their association to disease outcome (90)(91)(92)(93)(94)(95), and by 2021, one review performed a meta-analysis to evaluate the SNPs in malignancy (96). Up to now, three polymorphisms of IL-32 were found to be associated with the progression of several cancers that are rs28372698, rs12934561, and rs2015620 (Table 1).…”
Section: Implications Of Il-32 Polymorphisms In Cancermentioning
confidence: 99%
“…Recently, several studies have demonstrated the impact of IL-32 polymorphisms on cancer progression. Moreover, IL-32 SNPs were studied and reviewed with their association to disease outcome (90)(91)(92)(93)(94)(95), and by 2021, one review performed a meta-analysis to evaluate the SNPs in malignancy (96). Up to now, three polymorphisms of IL-32 were found to be associated with the progression of several cancers that are rs28372698, rs12934561, and rs2015620 (Table 1).…”
Section: Implications Of Il-32 Polymorphisms In Cancermentioning
confidence: 99%